Interstrand cross-linking reaction in triplexes containing a monofunctional transplatin-adduct. - Colombier, C (1996)
Our aim was to determine whether a single transplatin monofunctional adduct, either trans-[Pt(NH3)2(dC)Cl]+ or trans-[Pt(NH3)2(dG)Cl]+ within a homopyrimidine oligonucleotide, could further react and form an interstrand cross-link once the platinated oligonucleotide was bound to the complementary duplex. The single monofunctional adduct was located at either the 5' end or in the middle of the platinated oligonucleotide. In all the triplexes, specific interstrand cross-links were formed between the platinated Hoogsteen strand and the complementary purine-rich strand. No interstrand cross-links were detected between the platinated oligonucleotides and non-complementary DNA. The yield and the rate of the cross-linking reaction depend upon the nature and location of the monofunctional adducts. Half-lives of the monofunctional adducts within the triplexes were in the range 2-6 h. The potential use of the platinated oligonucleotides to modulate gene expression is discussed.